On the diagnosing algorithm for networks - Biasizzo, Anton; Novak, Franc (International journal of computer mathematics, 2000)
An example is given for which the diagnosing algorithm for networks, proposed by T. Kameda, S. Toida and F. J. Allan, fails to compute the correct system diagnosis. A correction of the algorithm is described.